DE-KULTURALISASI ISLAM DAN KONFLIK SOSIAL DALAM DAKWAH WAHABI DI INDONESIA - Saipul Hamdi (Jurnal Kawistara, 2019)
This article investigates the phenomena of a transnational Wahhabi movement particularly the Wahhabi local organization in Indonesia. Wahhabism is a puritan, textual, and reformist Islamic movement established in Nejd Saudi Arabia 18th century identified as part of the conservative Sunni orthodox tradition. It was determined as the major religious-state reference for shariah law formulation by the Saudi government and expanded to non-Arab countries around the world imposing reformation idea of Islamic religious tradition and academic culture. This article examines the expansion and growth of the Wahhabi local organization in Indonesia and the effort to perform deculturalization of Islam from the local religious tradition practices. Deculturalizing Islam or pulling out Islam from cultural mixture and absorption is not easy because Islam has integrated to the local religious tradition since its presence in the community around the 12th century, which shows a long negotiation and unification of those identities. In doing so, this article explores the response on Wahhabi deculturalization discourse and how the local people negotiate to this new identity and socio-religious transformation influenced by the Wahhabi’s teaching and ideology. The hypothesis of Wahhabi’s teaching position and role in shaping radicalism and terrorism has carried this research to understand the local context of Wahhabi in Indonesia, how the Wahhabi people understand and engage to radicalism and terrorism, the response to global jihadism propagation including Al-Qaeda and ISIS, and the production of Khilafah Islamiyah idea and mission. The aggressive approach of Wahhabi, which attacks a belief system of local Muslim practices and invigorates the new single identity of Islam, leads this article to investigate the patterns of Wahhabi socio-religious conflict in the communities and the influence to social disintegration existence.